The Utilization of Modified Cassava Flour (Mocaf) Industry Waste and Peat as Carrier of Nitrogen-Fixing Bacteria and Phosphate Solubilizing Bacteria Inoculant - RETNO ROSARIASTUTI; SUMANI SUMANI; SUPRIYADI SUPRIYADI; MUHAMMAD ARDIAN NURSETYAWAN; PRAMUSITA YOGA DANISWARA (Indonesian Society for microbiology, 2017)
Fertilizer demand in Indonesia increase for increasing agricultural production.Biofertilizer is organic fertilizer with the addition of specific microorganisms which are expected to reduce the amount of inorganic fertilizer. Carrier material plays an important role in maintaining the viability and storage period. Peat is used as a biofertilizer carrier for a long time. Solid waste of Modified Cassava Flour (Mocaf) which is the remainder of mocaf industry has great potential as a carrier material of good biofertilizers, because of its nutrient content. The aim of this study was determining the potential of mocaf solid waste and its combinations with peat as the carrier in supporting the growth of Nitrogen-fixing Bacteria (NFB) and Phosphate Solubilizing Bacteria (PSB) during the incubation of microorganisms. The experiment was conducted at the Laboratory of Soil Biology and Biotechnology, Faculty of Agriculture of Sebelas Maret University (UNS) using completely randomized design (CRD) with two factors of a carrier and incubation time as the experimental design. There were three types of carrier which have different combination. The base material were solid waste of Mocaf industry and peat. All materials of carrier were mixed and sterilized, than inoculated by Nitrogen- Fixing Bacteria (NFB) and Phosphate Solubilizing Bacteria (PSB) and incubated for 60 days. The growth of bacterias were analyzed every 15 days and the chemical composition of carrier were analyzed at the begin and the end of research (incubation). The results indicated that the incubation time significantlyaffected viability of NFB and PSB. Until 60th day incubation time, still showed the increasing growth of NFB and PSB.